Metabolomics profiling of extracellular metabolites in CHO-K1 cells cultured in different types of growth media - Mohamad Saberi, Salfarina Ezrina; Hashim, Yumi Zuhanis Has-Yun; Mel, Maizirwan; Amid, Azura; Ahmad-Raus, Raha; Packeer Mohamed, Vasila (Springer, 2013)
An efficient mammalian cell system for producing bioproducts should retain high cell viability and efficient use of energy sources rendering the need to understand the effects of various variables on the cell system. In this study, global metabolite (metabolomics) analysis approach was used to try and understand the relationships between types of media used, culture growth behavior and productivity. CHO-KI cells producing IGF-1 were obtained from ATCC and grown in T-flask (37 °C, 5 % CO2) until 70–80 % confluent in RPMI 1640 and Ham’s F12, respectively. Samples were taken at 8-hourly intervals for routine cell counting, biochemical responses, insulin like growth factor—1 (IGF-1) protein concentration and global metabolite analysis (gas chromatography mass spectrometry, GCMS). Conditioned media from each time point were spun down before injection into GCMS. Data from GCMS were then transferred to SIMCA-P + Version 12 for chemometric evaluation using principal component analysis. The results showed that while routine analysis gave only subtle differences between the media, global metabolite analysis was able to clearly separate the culture based on growth media with growth phases as confounding factor. Different types of media also appeared to affect IGF-1 production. Asparagine was found to be indicative of healthiness of cells and production of high IGF-1. Meanwhile identification of ornithine and lysine in death phase was found to be associated with apoptosis and oversupplied nutrient respectively. Using the biomarkers revealed in the study, several bioprocessing strategies including medium improvement and in-time downstream processing can be potentially implemented to achieve efficient CHO culture system.